Christ in the First Part of the Book of Gifts of Mar Šubhalmaran - James, Ken (Mayéutica, 2023)
The article only considers the first part of the Book of Gifts of Mar Šubḥalmaran and analyses some fundamental questions concerning the image of Christ that the author intends to transmit. This study is not concerned with the Christological controversies in the Syriac Churches during the sixth and seventh centuries. One of the peculiar characteristics of the Book of Gifts is that there is no explicit or implicit mention of any Christological arguments related to the debates of his time. The author's only intention is to guide the future generation of ascetics in their deep desire for union with Christ. This article intends to understand the underlying idea of the author on the gifts, how the gifts affect the life of the ascetics and the relevance of Christ in the overall argument of the first part of the Book of Gifts of Mar Šubḥalmaran.